Evaluation of E-Government Websites in Lesotho: An Empirical Study - MOLEFI LAWRENCE MATSIELI; RADHAMANY SOORYAMOORTHY (African Journal of Governance and Development, 2021)
Evaluation is essential for assessing the implementation and outcomes of programs for the purpose of informing decision making. However, although there are studies that evaluated e-government implementation in Lesotho, comprehensive studies are rare. This paper presents an empirical study of the evaluation of four websites of the ministries of the Government of Lesotho using content analysis. Since the website content analysis metrics and criteria are not entirely exhaustive, this study based the evaluation on four dimensions, namely, accessibility, usability, transparency and interactivity. The findings indicate that the ministerial websites of the Government of Lesotho are falling short in addressing these issues. The evaluation results highlight that the web information and features that are key in fostering accessibility, usability, transparency and interactivity of government services are insufficient or completely non-existent in the ministerial sites. The government must focus more efforts on improving these sites to enhance accountability and restore citizen trust in government and confidence in public administration.